Innovations in Spanish Lexicography: The Diccionario Digital del Español (DIDES) - Fuertes Olivera, Pedro A. (Círculo de Lingüística Aplicada a la Comunicación, 2025)
In 2014, the International Centre for Lexicography, a research group at Valladolid signed a contract with Ordbogen A/S (a Danish language technology company) and the University of Valladolid for developing a lexicographic project, the so-called Diccionarios Valladolid-UVa (Fuertes-Olivera 2019 and 2022; Fuertes-Olivera & Tarp, 2022; Fuertes-Olivera et al, 2018; Tarp and Fuertes-Olivera, 2016). Each partner gave around 180,000 euros (the International Centre for Lexicography’s contribution came from the research projects FFI2011-22885, VA067A12-1 and FFI2014-52462-P), to be employed in the design and construction of Spanish dictionaries (in particular, a general dictionary of Spanish, a Spanish dictionary of accounting, a bilingual Spanish-English/English-Spanish dictionary and a bilingual Spanish-English/English-Spanish accounting dictionary). By the end of 2019, the Spanish Research Agency and the regional one had stopped funding the research projects of the International Centre for Lexicography, which prompted a change of course in the project and the actual dismemberment of the research group. At that time, the project had completed around 50,000 dictionary articles and was cooperating with Ordbogen in launching in Spain Write Assistant, an integrated writing and translation tool (Fuertes-Olivera and Tarp, 2020). In July 2020, the editor of the project decided to continue working on it, concentrating on three tasks. Firstly, he was going to create more dictionary articles for the general dictionary of Spanish (i.e., the accounting and bilingual projects were abandoned). Secondly, he would accommodate the existing dictionary articles to the new ones to new findings (Tarp, 2022). And finally, both he and Sven Tarp would explore a way ahead for making the lexicographic data truly innovative and developing more effective products, services, processes, technologies, and business models. This article explains decisions concerned with the Diccionario Digital del Español (DIDES, the name given to the general dictionary of Spanish of the abovementioned lexicography project is accessed at https://diesgital.com). This online dictionary was released by Ordbogen in June 2023, and some of its innovations are concerned with the following: (a) selection of lemmas; (b) social mores; (c) the use of the Internet as a lexicographic source; (d) the treatment of lexicographic data; (e) the use of technology for searching, presenting, and updating the dictionary articles; and (f) the introduction of new business models. Since August 2023, I am also using generative Artificial Intelligence for crafting definitions and completing the lexicographic data of each dictionary article. For reasons of space, I have decided to explain how this innovation works in future articles.